How climate change interacts with inequity to impact nutrition - Salm, Leah; Nisbett, Nicholas; Cramer, Laura K.; Gillespie, Stuart; Thornton, Philip K. (2019)
Climate change is affecting patterns of inequity and inequality. People will experience climate change differently not only because of where they live, but because of who they are – because they grew up in poverty, or because of their gender, caste, ethnicity, age, sexuality or disability.